Buckling Analysis of Functionally Graded Materials (FGM) Thin Plates with Various Circular Cutout Arrangements - Alashkar, Adnan (2022)
In this paper, several analyses were conducted to investigate the buckling behavior of Functionally Graded Material (FGM) thin plates with various circular cutout arrangements. The computer model was simulated using the Finite Element (FE) software ABAQUS. The developed model was validated by the authors in previous research. A parametric analysis was employed to investigate the effect of plate thickness and circular cutout diameter on the buckling behavior of the FGM thin plates. The normalized buckling load was also calculated to compare the buckling performance of FGM plates with various dimensions. Moreover, von Mises stress analysis was examined to understand the yield capability of the FGM plates in addition to the buckling modes that show the stress distribution of the critical buckling stress. Hence, this research provides a comprehensive analysis to display the relation between the critical buckling load and the arrangement of the circular cutouts. The results show that the critical buckling load heavily depends on the dimension of the plate and the cutout size. For instance, an increase in the plate thickness and a decrease in the cutout diameter increase the critical buckling load. Moreover, the circular cutout in a horizontal arrangement exhibited the best buckling performance, and as the arrangement shifts to a vertical arrangement, the buckling performance deteriorates.